Overweight and obesity in south central Uganda: A population-based study - Adeoluwa Ayoola; Robert Ssekubugu; Mary Kathryn Grabowski; Joseph Ssekasanvu; Godfrey Kigozi; Aishat Mustapha; Steven J. Reynolds; Anna Mia Ekstrom; Helena Nordenstedt; Rocio Enriquez; Ronald H. Gray; Maria J. Wawer; et al. (Public Library of Science (PLoS), 2022)
Obesity is a rapidly growing global health challenge, but there are few population-level studies from non-urban settings in sub-Saharan Africa. We evaluated the prevalence of overweight (body mass index (BMI)>25 kg/m2), obesity (BMI>30 kg/m2), and associated factors using data from May 2018 to November 2020 from the Rakai Community Cohort Study, a population-based cohort of residents aged 15 to 49 living in forty-one fishing, trading, and agrarian communities in South Central Uganda. Modified Poisson regression was used to estimate adjusted prevalence risk ratios (PRR) and 95% confidence intervals (CI) in 18,079 participants. The overall mean BMI was 22.9 kg/m2. Mean BMI was 21.5 kg/m2 and 24.1 kg/m2 for males and females, respectively. The prevalence of overweight and obesity were 22.8% and 6.2%, respectively. Females had a higher probability of overweight/obesity (PRR: 4.11, CI: 2.98-5.68) than males. For female participants, increasing age, higher socioeconomic status, residing in a trading or fishing community (PRR: 1.25, CI 1.16-1.35 and PRR: 1.17, CI 1.10-1.25, respectively), being currently or previously married (PRR: 1.22, CI 1.07-1.40 and PRR: 1.16, CI 1.01-1.34, respectively), working in a bar/restaurant (PRR: 1.29, CI 1.17-1.45), trading/shopkeeping (PRR: 1.38, CI 1.29-1.48), and reporting alcohol use in the last year (PRR: 1.21, CI 1.10-1.33) were risk factors for overweight/obese. For male participants, increasing age, higher socioeconomic status, being currently married (PRR: 1.94, CI 1.50-2.50), residing in a fishing community (PRR: 1.68, CI 1.40-2.02), working in a bar/restaurant (PRR: 2.20, CI 1.10-4.40), trading/shopkeeping (PRR: 1.75, CI 1.45-2.11), or fishing (PRR: 1.32, CI 1.03-1.69) increased the probability of overweight/obesity. Non-Muslim participants, male smokers, and HIV-positive females had a lower probability of overweight/obese. The prevalence of overweight/obesity in non-urban Ugandans is substantial. Targeted interventions to high-risk subgroups in this population are needed.